S43 Circulatory levels of microrna-34a expression identify patients with poor clinical outcome, and regulate pulmonary vascular cell phenotype. (December 2018) - Lin, J; Iremonger, J; Pickworth, J; Rothman, A; Casbolt, H; Arnold, N; Elliot, C; Condliffe, R; Kiely, D; Jing, ZC; Lawrie, A
Abstract : Introduction: Despite current therapies for pulmonary arterial hypertension (PAH), vascular endothelial dysfunction (endothelial-mesenchymal transition, EndoMT) along with hyperproliferative pulmonary vasculopathy persist. Circulatory microRNAs (miRs) offer considerable promise as both a prognostic biomarker, and to identify molecular mechanisms underlying PAH. Previous study from our lab identified whole blood miR-34a as downregulated in patients with PAH. Aims: 1) To assess and validate changes in circulatory miR-34a-5p and miR-34a-3p in patients with PAH, and 2) To investigate the role of miR-34a in pulmonary artery smooth muscle cells (PASMC) proliferation and in EndoMT of pulmonary artery endothelial cells (PAEC). Methods: The level of circulatory miR-34a expression was first measured using qRT-PCR in rodent animal models and age-sex matched healthy volunteers (HV) and IPAH patients from Sheffield, UK (plasma, HV, n=29, IPAH, n=27; whole blood, HV, n=11, IPAH, n=14), and then validated in another cohort from Beijing, China (plasma, HV, n=19, IPAH n=36; whole blood, HV=20, IPAH, n=39). The effect of miR-34a on cell proliferation, apoptosis, migration and endothelial-mesenchymal transition (EndoMT) were assessed in human PASMC and PAEC following transfection of either miR-34a-5p and miR-34a-3p mimics or antagonists, or scrambled miR. Results: Circulatory levels of miR-34a-5p and 3 p expression are downregulated in both IPAH patients and preclinical models of PAH. Reduced whole blood miR-34a-5p levels are associated with disease severity and poor survival. Transfection of PASMC with miR-34a-5p or −3 p antagonists promote PASMC proliferation and suppress apoptosis. In contrast, miR-34a-5p and −3 p mimics suppress PASMC proliferation and promote apoptosis. Transfection of PAEC with miR-34a-5p or −3 p mimics suppress EndoMT induced by combinatorial stimulation of TGF-beta1, IL-1beta and TNF-alpha, assessed by reduced EndoMT markers (alpha-SMA, Vimentin and Zeb1) and increased endothelial marker (VWF and CD31). Conclusion: This research identifies miR-34a as a key miR in the regulation of pulmonary vascular cell phenotype associated with the pathogenesis of PAH. Circulating levels of miR-34a could be a potential tool to stratify patients for treatments addressing PASMC proliferation and EndoMT. Further experiments in preclinical models are currently underway.